2015
DOI: 10.4314/jfas.v6i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper on Passivity and Corrosion Behavior of Fe-xC-5Cu Alloy

Abstract: ABSTRACT:The correlation between corrosion behavior rate of annealed Fe-xC-5Cu alloys and their microstructure and phase composition is presented. The metallurgical analyses, including, XRay diffraction (XRD), the scanning electron microscopy (SEM) with energy dispersive analysis (EDX), and induction hardening characterization are conducted to study the Fe-C-Cu alloys. Corrosion parameters in H2SO4 1N solution have been established by carrying out electrochemical studies such as potentiodynamic (Tafel polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, the insufficient recycling process led to the steel scrap usually contain copper as a common tramp element. Copper might be present in the steel scrap unintentionally, as well as it might be added to certain steels intentionally as an alloying element for reaching the required mechanical properties and increasing the corrosion effect [1][2][3][4]. The negative impact of copper on the mechanical properties of steel, especially at surface treatment processes under high temperatures has been discussed for a long time [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the insufficient recycling process led to the steel scrap usually contain copper as a common tramp element. Copper might be present in the steel scrap unintentionally, as well as it might be added to certain steels intentionally as an alloying element for reaching the required mechanical properties and increasing the corrosion effect [1][2][3][4]. The negative impact of copper on the mechanical properties of steel, especially at surface treatment processes under high temperatures has been discussed for a long time [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Organic nitrogen-based compounds such as amines and their salts have been used successfully as corrosion inhibitors in oilfield systems. In previous work, the mode of action of some amines to protect metals and alloys has been studied [2][3][4][5][6][7][8][9].These compounds adsorb on the metal surface and suppress metal dissolution and reduction reactions. D.P 978 Schweinsberg et al [10] found that the action of n-alkyl quaternary ammonium iodides is caused by the alkyl chain and this is attributed to van der Waals' forces.…”
Section: Introductionmentioning
confidence: 99%